A study of safety work methods in the construction industry-perspective CIDB - Che Shafee, Muhammad Shazmie; Salleh, Nurul Azita (2015)
This study about to solve problems related to the safety work method in the construction industry. This study was conducted to identify the problem occurred among workers at the construction industry in Malaysia, to propose the safety work method in the construction industry and to develop a new model of safety work method in the construction industry.Data collection will be conducted by using qualitative methods by interview CIDB construction personnel.The expected finding from this study is can provide a solution for reduced the problem accident among workers construction site for give the best protection while at the site. The conclusion, the contribution from this study is to develop a new model to reduce the problem about safety work in the construction building industry in the Malaysia.This study also can interpret or give scenario the good safety work method in the construction industry can reduce the accident at the site.The significant from this study is can provide a method for safety workers for reduce the accident at construction site, can give a clear picture about the methods use to improve the safety works and to emphasize the personnel construction to carry out these methods on an ongoing basis at the construction site.